Tindak Tutur Direktif dalam Interaksi Tenaga Kesehatan terhadap Pasien di Puskesmas Singgani Kota Palu - Neneng Atriani AR; Julia Marfuah (Jurnal Kreatif Online, 2023)
This study aims to describe the form, function, and strategy of directive speech acts in the interaction of health workers with patients at the Singgani Health Center, Palu City. This study used qualitative research methods. The data in this study were in the form of oral data contained in conversations spoken by health workers and patients at the Singgani Health Center, Palu City. The data was collected using observation techniques, recording, observing, recording then followed by data reduction, data presentation, interpreting meaning, and drawing conclusions. Based on the research results, 13 data were found in the form of directive speech acts namely, 3 forms of prohibition, 5 forms of advice, 2 forms of requests, 1 form of invitation, and 2 forms of orders. 10 directive speech act function data, namely 2 prohibition functions,                 2 advisory functions, 3 solicitation functions, 1 request function, 2 command functions. 10 directive speech act strategy data, namely 6 direct strategies and 4 indirect strategies.